Odpowiedzi

2009-12-04T20:09:31+01:00
A)

Al(III)(N(V)O3)3(-II),

Ca3(II)(P(V)O4)2(-II),

H(I)N(V)O3(-II),

Mg(II)S(-II)


b)

H(I)Cl(VII)O4(-II),

Si(IV)O2(-II), H(I)Br(-I), Na(I)H(-I)

c)

Zn2+(II),

C(IV)O3 2-(-II),

H(I)S(VI)O4-(-II),

Cu+(I),

Mn(VII)O4- (-II)

Pozdro))
12 4 12
2009-12-04T20:35:36+01:00
III x (-II)
a) Al(NO₃)₃
III+3*x+3*(-II)=0
III+3x+(-VI)=0
-III+3x=0
3x=III /:3
x=I

II x (-II)
Ca₃(PO₄)₂
3*II+2*x+2*4*(-II)=0
2x+X=0 /:2
2x=(-X)
x=(-V)


I x (-II)
HNO₃
I+x+3*(-II)=0
I+x+(-VI)=0
x+(-V)=0
x=V


II x
MgS
II+x=0
x=(-II)

b)
I x (-II)
HClO₄
I+x+4*(-II)=0
x+(VII)=0
x=VII

I x
HBr
I+x=0
x+(-I)

x I
NaH
x+I=0
x=(-I)

x (-II)
SiO₂
x+2*(-II)=0
x+(-IV)=0
x=IV

nad c) musze pomysleć :P

hmm
x
Zn²⁺
x=II

x (-II)
CO₂-3
x+2*(-II)=(-III)
x+(-IV)=(-III)
x=III

I x (-II)
HSO-4
I+x+(-II)=(-IV)
II+x+(-II)=(-IV)
x=(-IV)

x (-II)
MnO-4
x+(-II)=(-IV)
x=(-IV)+II
x=-II


x
Cu⁺
x=I

jak cos niejasno napisane to pisz wyjaśnie:)

41 3 41